Melatonin Decreases Levels of S100β and NFκB, Increases Levels of Synaptophysinina Rat Model of Alzheimer's Disease - Jun, Zhou; Li, Zhou; Fang, Wang; Fengzhen, Yang; Puyuan, Wen; Wenwen, Li; Zhi, Song; C. Bondy, Stephen (Current Aging Science, 2013)
The effect of treatment with melatonin was investigated in a rat model of Alzheimer’s disease (AD) involving a single intra-hippocampal injection of amyloid peptide Aβ1-42. Thirty days after this injection immunohistochemical analysis revealed significant increases of both S-100β and NFκB in cortex and hippocampus of treated animals. Levels of synaptophysin were depressed following treatment and this was confirmed by Western blotting. Histopathological studies revealed a diminution of neuronal cell number in the CA3 area of the hippocampus. Behaviorally, the rate of learning escape from electroshock using a maze box was diminished in Aβ-treated mice. Another group of Aβ treated also received an oral gavage of 0.5 mg/kg melatonin on each of the 30 days between Aβ treatment and sacrifice. The effect of this repeated melatonin exposure was to reverse Aβ-induced changes in CA3 cell number and S-100 levels. The increased cerebral content of NF-κB and the behavioral changes caused by Aβ treatment were partially reversed by melatonin. However, melatonin administration had no effect on the reduced level of synaptophysin in Aβ-treated mice. Overall, these findings suggest that melatonin may exert a potentially beneficial effect upon the progression of AD.
Keywords: melatonin